The effect of salinization in maintenance of intermittent catheter - Gil,Nelly Lopes de Moraes (2008)
The aim of this study was to carry out a comparative analysis between the intermittent catheter, filled with heparin 100 U/ml and one filled with saline solution 0.9%., by evaluating the formation of clots and quantifying them, when detected. Four groups of seven rabbits were used. In two of the groups, saline solution was used; in one group, in case of resistance, it was forced, whereas in the other, it was not forced. The other two groups were subjected to the same procedure, but, heparin solution was used. The presence of clot formation in all the groups was observed, independently of the solution used.